Avaliação da influência da postura na articulação temporomandibular e o papel da fisioterapia associada à odontologia em pacientes portadores de disfunção temporomandibular - Guimarães, Elcio Alves (2017)
Introduction: The temporomandibular joint (TMJ) is an element of the Stomatognathic System, capable of performing complex movements, being responsible for mastication, swallowing and speech. Temporomandibular dysfunction (TMD) is a joint disorder associated with the stomatognathic system and with a series of symptoms. As a compensatory mechanism, there might be changes in the body posture. It requires complex and multifactorial treatment. Objectives: Comparing the muscular activity, by means of an Electromyography of orofacial muscles and the Maximum Bite Force in symptomatic patients in different positions, before and after physical therapy. Observing the immediate effect of treatment on patients' pain. Methods: Patients with TMD were submitted to a muscular activity evaluation by means of an Electromyography of orofacial muscles and evaluation of Maximum Muscular Strength through the Gnatodinamometer, in the lying, sitting and standing body positions. It was followed by physical therapy treatment using Osteopathy. Then it was evaluated the muscular activity and the maximum muscular strenght in the 03 decubitus positions. Results: Posture affects significantly the activity of the orofacial muscles depending on the condition that the patient is exposed to and the moment in which the evaluation is done. The result shows that there is a difference between position and condition variables as also in condition and moment variables, showing that the treatment was efficient when compared to the patient's condition. Significant pain relief. Conclusion: We conclude that the posture influences the TMJ, the standing position being the one with the highest muscle contraction and maximum bite force. Physiotherapy is fundamental in the treatment of TMD with Dentistry, always associated with an interdisciplinary team.